Application of Cryopreserved Amniotic Membranes In Therapy of Neurotrophic Ulcers - Royenko, Aleksandr A.; Prokopyuk, Vladimir Yu.; Falko, Oksana V.; Shevchenko, Nadezhda A.; Volina, Viktoriya V.; Prokopyuk, Olga S. (Problems of Cryobiology and Cryomedicine, 2015)
N/A